Risk factors for bacterial vaginosis among Indonesian women (Medical Journal of Indonesia, 2010)
Aim To identify risk factors for bacterial vaginosis (BV) among Indonesian women. Methods This is a cross sectional study involving 492 women with age ranged 15-50 years. Vaginal discharge was collected. Whiff test and Nugent scoring were utilized to identify BV. Settings are Puskesmas Karawang, Pedes, Cikampek,Tempuran, Batalyon 201 Clinic Cijantung, Faculty of Medicine University of Indonesia and Cipto Mangunkusumo Hospital. Results Age of the subjects were 15-25 years old (26.8%), 26 - 40 years old (59.1%), and > 40 years old (14%). The mean age was 30.9 years. Marital status of the subjects were not-married (16.9%), married (76.4%), married more than once (6.7%). Prevalence of bacterial vaginosis in this study was 30.7% according to Nugent's score. Age > 40 years old (OR=3.15 IK 95% = 1.15-1.48) and uncircumcised couple (OR=6.25, IK 95% = 2.54 - 15.38) were independently and significantly associated with incidence of BV (p<0.05). Conclusions Prevalence of BV in this study was 30.7%. Determinant risk factors of BV were age and uncircumcised sexual partner. (Med J Indones 2010; 19:130-5)